Manual of engineering drawing : technical product specification and documentation to British and international standards /: technical product specification and documentation to British and international standards. (2020) - Simmons, C. H (Colin H.); IEng MIED, Phelps, Neil; Maguire, D. E (Dennis E.)
No abstract available